PENGKAJIAN POTENSI, KENDALA DAN PELUANG PENGEMBANGAN PALAWIJA DI PAPUA - Afrizal Malik; Jermia Limbongan (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
In general the assessment aims to investigate the development potency, threat and opportunity of secondary crops especially of corn, soybeans and groundnut in Papua. In particular, the research is to study to what extent the existing technology can be applied by farmers and its probability to the future development. The assessment was conducted in 2006, covering two regions of secondary crops namely Jayapura and Keerom's regency. Data collection was conducted through a survey by involving 190 farmers of corn, soybeans and groundnut which were chosen by simple random design method. Qualitative and quantitative approach were used for data analyses and the results were: (1) The performance of farming systems of corn, soybeans and groundnut in Papua is relatively low due to the low technology adoption, (2) The potency for secondary crops development in Papua still growing up, based on economic, natural resource and conducive agro-climate. The use of such relatively small potency lead to a wide open of opportunity to increase productivity performance of secondary crops i.e. corn, soybeans and groundnut in Papua, (3) the constraint in developing secondary crops is not only caused by economic aspect of farmers but also by low ability and skill of farmers as well as insufficient number of agricultural manpower. To increase productivity and secondary crop products in Papua we need to establish steps to increase the land optimalisation, the introduction of cultivation technology, the improvement of agricultural extension worker and the initiation of micro financial institution growth to accommodate farmers' need i.e. Agricultural Micro Financial Institute Key words: Secondary crops, potency, opportunity, threats, Papua   Pengkajian ini secara umum bertujuan untuk mengetahui potensi, kendala dan peluang pengembangan palawija di Papua. Secara khusus, mempelajari sejauhmana teknologi yang telah diterapkan petani saat ini dan kemungkinan pengembangannya ke depan. Pengkajian dilakukan pada bulan Juni-September 2006 di dua kabupaten sentra palawija yaitu Kabupaten Jayapura dan Keerom Provinsi Papua. Pengumpulan data dilakukan melalui survai terhadap 190 petani jagung, kedelai dan kacang tanah yang terpilih secara acak sederhana sebagai responden. Analisis data dilakukan secara deskriptif kualitatif dan kuantitatif. Hasil kajian menunjukkan: (1) Kinerja usahatani palawija khususnya jagung, kedelai dan kacang tanah di Papua masih relatif rendah, karena penerapan teknologinya rendah. Kendalanya bermuara pada kemampuan modal petani yang lemah, (2) Potensi pengembangan palawija di Papua masih besar, baik ditinjau dan aspek ekonomi maupun ketersediaan sumberdaya alam dan dukungan agroklimat yang kondusif. Pemanfaatan potensi tersebut masih relatif kecil, sehingga terdapat peluang yang besar untuk meningkatkan kinerja produksi pertanian di wilayah ini khususnya jagung, kedelai dan kacang tanah, (3) Kendala pengembangan palawija selain faktor ekonomi, juga rendahnya tingkat pengetahuan petani dan kekurangan tenaga kerja pada saat diperlukan. Untuk lebih meningkatkan produktivitas dan produksi palawija di Papua diperlukan langkah peningkatan optimalisasi pemanfaatan lahan potensial dan introduksi inovasi teknologi budidaya, peningkatan kinerja penyuluh pertanian dan inisiasi tumbuhnya kelembagaan jasa keuangan yang dapat mengakomodasi kebutuhan petani, yaitu Lembaga Keuangan Mikro (LKM) pertanian. Kata kunci: Palawija, potensi, peluang, kendala, Papua